Electrical Transmission and Substation Structures 2018 : dedicated to strengthening our critical infrastructure : proceedings of the Electrical Transmission and Substation Structures Conference 2018 : November 4-8, 2018, Atlanta, Georgia - Miller, Michael (American Society of Civil Engineers, 2018)
This collection contains 46 peer-reviewed papers on transmission line and substation structures and foundation construction issues presented at the Electrical Transmission and Substation Structures Conference 2018, held in Atlanta, Georgia, November 4-8, 2018. Topics include: structural analysis; foundations; structural failure analysis and investigation; substation design issues; seismic and special design considerations; structure upgrading; and construction challenges.